2020
DOI: 10.21037/jtd-20-2436
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of postoperative recurrence of primary spontaneous pneumothorax

Abstract: Background: Spontaneous pneumothorax is common in relatively young, healthy patients. The risk factors for postoperative recurrence after correction are not fully understood. Methods: We retrospectively reviewed the records of patients who underwent surgery for spontaneous pneumothorax between January 2006 and October 2017. We assessed the possible factors causing postoperative recurrence using univariate and multivariate analyses. We then used the inverse probability of treatment-weighted method to correct fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
0
9
1
1
Order By: Relevance
“…Previous studies have reported that surgery could be a risk factor for recurrence, not improving prognosis [14,28,29]. The recurrence rates in the young population who underwent surgery tended to increase [14]. In our study, with a few exceptions, PSP patients with surgical intervention experienced increased risk over those who had not been treated surgically.…”
Section: Discussioncontrasting
confidence: 44%
“…Previous studies have reported that surgery could be a risk factor for recurrence, not improving prognosis [14,28,29]. The recurrence rates in the young population who underwent surgery tended to increase [14]. In our study, with a few exceptions, PSP patients with surgical intervention experienced increased risk over those who had not been treated surgically.…”
Section: Discussioncontrasting
confidence: 44%
“…However, the protective effect of surgery has remained a controversial issue 8 , 20 , 30 . Previous studies have reported that surgery could be a risk factor for recurrence, not improving prognosis 14 , 30 , 31 . The recurrence rates in the young population who underwent surgery tended to increase 14 .…”
Section: Discussionmentioning
confidence: 93%
“…Regarding pleurodesis, thoracoscopy is therefore proposed as a first-line procedure in many European countries. However, recurrence rate which was significantly higher after thoracoscopy compared to thoracotomy [ 139 141 ].…”
Section: Summary Of the Resultsmentioning
confidence: 99%